Associations of Reactive Thrombocytosis With Clinical Characteristics in Pediatric Diseases - Jinn-Li Wang; Liang-Ti Huang; Kuan-Hsun Wu; Hui-Wen Lin; Man-Yan Ho; Hsingjin Eugene Liu (Pediatrics and Neonatology, 2011)
Reactive thrombocytosis (RT) in pediatric patients is common, but usually without symptoms. The incidence of RT is different depending on age. Mostly, we reason that RT is a phenomenon, nevertheless the diagnostic value of RT is little known. Therefore, the aim of this study was to determine the association of RT and clinical or laboratory characteristics in pediatric diseases. Methods: We retrospectively analyzed the medical records of pediatric patients hospitalized at Wan Fang hospital from January 2002 to July 2009. Thrombocytosis was defined as a platelet count more than 500×109/L. There were 822 patients enrolled to this study. The clinical parameters, including age, gender, disease type, and hospitalization days, were investigated. The association between RT and clinical manifestations and the relationship of leukocytes, hemoglobin, C-reactive protein, and platelet counts were analyzed. Results: The overall incidence of RT in hospitalized pediatric patients was 6.3%. Infants had a significantly higher incidence (11.3%, p<0.001). Mild RT was found in most patients (83.6%). Infections (75.4%) were the most common cause, followed by perinatal diseases (11.1%). The relationship of RT and age revealed a positive correlation (p=0.045, r=0.70 after adjustment). The degree of RT was an independent factor for hospitalization days (p<0.001, r=0.126 after adjustment). There was a positive correlation between white blood cell count and platelets (p=0.002, r=0.017); on the contrary, the relationship between hemoglobin level and platelets was an inverse correlation (p<0.001, r=−0.193). Conclusions: In children, the degree of RT was associated with age, and patients had significantly longer hospitalization days in proportion to the increase in platelet count. Laboratory association revealed that the degree of RT was positively correlated to white cell count and negatively correlated to hemoglobin level. Therefore, the degree of RT might be a predictive factor with regard to hospitalization days in pediatric diseases.